Perancangan Sistem Informasi Penjualan Barang Pada Toko Simarmata Berbasis Web - Simarmata, Ester Agustine; Hutapea, Marlyna Infryanty; Saragih, Rijois I. E. (Universitas Methodist Indonesia, 2024)
Toko Simarmata is a business engaged in the business of selling daily necessities. The store has quite a lot of customers who come to buy various kinds of needs ranging from snacks, drinks and household supplies. However, the store is in the process of processing its transactions, such as the preparation of goods data which includes prices, and all sales transactions are still manually recorded in the book. This often causes problems such as the loss of sales data which causes re-recording so that the resulting report is not perfect. Therefore, a web programming system is needed which has the aim of making it easier for Simarmata Shop owners to solve the problems that occur, such as storing data on goods sales transactions, knowing sales reports that occur within a certain time frame, consumers who can order the desired items through the website and payments that can be made non-cash without the need to come directly to the store. The design of this Information System is of course based on using direct observation methods and interviews with shop owners. So as to produce a Sales Information System at a web-based Simarmata Store that suits the needs of the store.